Anti Ulcerogenic And Ulcer Healing Studies Of Aqueous Extract Of Pueraria Tuberosa Leaves On Rats - SUMALATHA GINDI; BAHLUL Z AWEN; CHANDU BABURAO; MUKKANTI KHAGGA (International Journal of Pharma and Bio Sciences, 2010)
In this study, the anti ulcerogenic effect of water extract obtained from the leaves of Pueraria Tuberosa[PT] was investigated using cold restraint stress(CRU), pyloric ligation(PL) & Ethanol induced (EtOH) induced gastric ulcer models in rats. The treatment with PT at higher dose significantly inhibited gastric lesions induced by CRU (76.6%), PL (80.1%) & EtOH (70.6%) respectively with equal potency of Omeperazole. In addition the effects of PT on H+K+ATPase activity was determined. PT significantly inhibited H+K+ATpase activity in EtOH induced ulcer model. PT accelerated the healing of EtOH induced ulcers by inhibiting H+K+ATPase activity.